Incidencia del control interno en el área de logística-abastecimiento de la Municipalidad Distrital de Guadalupe año 2018 - Vásquez Mendoza, Franklin (2019)
This research work entitled Incidence of Internal Control in the Logistics-Supply area of the District Municipality of Guadalupe in 2018 focuses on making an evaluation and analysis of internal control with respect to the orders that the area as such executes. The District Municipality of Guadalupe has shown to be involved in purely traditional and unprofessional processes and all this due to rejection of the new administrative provisions, which affects the performance of optimal management.The type of research is descriptive because it is interested in knowledge and is complemented with techniques for data collection such as: interviews, questionnaires, direct observation. The most relevant conclusion of this research is that internal control significantly affects the improvement of the Logistics-Supply Area of the District Municipality of Guadalupe.